2022
DOI: 10.3389/fcvm.2022.790044
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Model for Acute Kidney Injury After Pericardiectomy: An Observational Study

Abstract: ObjectivesAcute kidney injury is a common complication after pericardiectomy for constrictive pericarditis, which predisposes patients to worse outcomes and high medical costs. We aimed to investigate potential risk factors and consequences and establish a prediction model.MethodsWe selected patients with constrictive pericarditis receiving isolated pericardiectomy from January 2013 to January 2021. Patients receiving concomittant surgery or repeat percardiectomy, as well as end-stage of renal disease were exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Several other studies reported that preexisting CKD was a risk factor for AKI after surgery. [20][21][22] Fontecha-Barriuso et al 23 reviewed the relationship of pre-existing CKD with post-surgical AKI and found that these patients had increased risk of AKI. CKD is characterized by progressive and irreversible loss of kidney function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other studies reported that preexisting CKD was a risk factor for AKI after surgery. [20][21][22] Fontecha-Barriuso et al 23 reviewed the relationship of pre-existing CKD with post-surgical AKI and found that these patients had increased risk of AKI. CKD is characterized by progressive and irreversible loss of kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies used nomogram models to assess the risk of AKI after surgery, and these models had good performance, but they did not focus on patients receiving hip fracture surgery. 20,21 In particular, Yu et al examined patients undergoing liver resection 20 and Wang et al examined patients undergoing pericardiectomy. 21 Our nomogram model incorporated preoperative and perioperative factors in patients undergoing hip fracture surgery and showed good performance in the internal and external validation.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang's team from West China Hospital even established a predictive model incorporating 10 predictors; this model could be used not only for predicting AKI after on-pump cardiac surgery but also for predicting the severity of AKI, and external validation was successful (1). Wang and colleagues from Peking Union Medical College Hospital established a model for predicting AKI after pericardiectomy (22). However, due to the rarity of comorbid CTD, risk factors for postoperative AKI occurrence in patients with CTD undergoing on-pump cardiac surgery were not available in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, preventing the development of acute renal injury after cardiac surgery, optimizing pre-, intra-and post-operative factors, to reduce acute renal injury, contribute to better postoperative results, and reduce the rate of acute renal injury, morbidity, and mortality. 45,46 Strengths and limitations of pericardiectomy with or without cardiopulmonary bypass were showed in Table 1.…”
Section: Postoperative Acute Kidney Injurymentioning
confidence: 99%